Novel secretory protein Ss-Caf1 of the plant-pathogenic fungus Sclerotinia sclerotiorum is required for host penetration and normal sclerotial development - Xiao, Xueqiong; Xie, Jiatao; Cheng, Jiasen; Li, Guoqing; Yi, Xianhong; Jiang, Daohong; Fu, Yanping (Molecular plant-microbe interactions, 2014)
To decipher the mechanism of pathogenicity in Sclerotinia sclerotiorum, a pathogenicity-defective mutant, Sunf-MT6, was isolated from a T-DNA insertional library. Sunf-MT6 could not form compound appressorium and failed to induce lesions on leaves of rapeseed though it could produce more oxalic acid than the wild-type strain. However, it could enter into host tissues via wounds and cause typical necrotic lesions. Furthermore, Sunf-MT6 produced fewer but larger sclerotia than the wild-type strain Sunf-M. A gene, named Ss-caf1, was disrupted by T-DNA insertion in Sunf-MT6. Gene complementation and knockdown experiments confirmed that the disruption of Ss-caf1 was responsible for the phenotypic changes of Sunf-MT6. Ss-caf1 encodes a secretory protein with a putative Ca(2+)-binding EF-hand motif. High expression levels of Ss-caf1 were observed at an early stage of compound appressorium formation and in immature sclerotia. Expression of Ss-caf1 without signal peptides in Nicotiana benthamiana via Tobacco rattle virus-based vectors elicited cell death. These results suggest that Ss-caf1 plays an important role in compound appressorium formation and sclerotial development of S. sclerotiorum. In addition, Ss-Caf1 has the potential to interact with certain host proteins or unknown substances in host cells, resulting in subsequent host cell death.